Theoretical Study of the π-Bridge Influence with Different Units of Thiophene and Thiazole in Coumarin Dye-Sensitized Solar Cells - Rody Soto-Rojo; Jesús Baldenebro-López; Daniel Glossman-Mitnik (International Journal of Photoenergy)
Eight coumarin derivative dyes were studied by varying the π-bridge size with different thiophene and thiazole units for their potential use in dye-sensitized solar cells (DSSC). Geometry optimization, the energy levels and electron density of the Highest Occupied Molecular Orbital and the Lowest Unoccupied Molecular Orbital, and ultraviolet-visible absorption spectra were calculated by Density Functional Theory (DFT) and Time-Dependent-DFT. All molecular properties were analyzed to decide which dye was the most efficient. Furthermore, chemical reactivity parameters, such as chemical hardness, electrophilicity index, and electroaccepting power, were obtained and analyzed, whose values predicted the properties of the dyes in addition to the rest of the studied molecular properties. Our calculations allow us to qualitatively study dye molecules and choose the best for use in a DSSC. The effects of π-bridges based on thiophenes, thiazoles, and combinations of the two were reviewed; dyes with three units mainly of thiazole were chosen as the best photosensitizers for DSSC.